Catabolite Repression in the d-Serine Deaminase System of Escherichia coli K-12 - McFall, Elizabeth (1971)
The induced synthesis of d-serine deaminase in Escherichia coli is subject to three catabolic effects: inhibition on inducer uptake, transient repression, and catabolite repression. Inhibition on d-serine uptake is not significant at the d-serine concentration normally used for induction. Transient repression and catabolite repression of d-serine deaminase synthesis are abolished by mutations in dsdCy, which appears to be an operator locus. The decline in the rate of constitutive synthesis observed in dsdCx mutants growing with glycerol as carbon source at temperatures above 37 C is due to catabolite repression. The low level of constitutivity at 37 C and the partial cis dominance of dsdCx mutants are not artifacts of catabolite repression. It is suggested that a product of one of the genes of the dsd operon may regulate the expression of the operon.